Kiprah KH. Sahal Suhana Tokoh Pendiri Pendidikan Islam Modern di Kabupaten Kuningan Jawa Barat, 1994-2016 - Khodijah, Siti; Marta, Nur Aeni; Abrar, Abrar (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
Education in Indonesia has a long history of producing intellectual figures from local to national. In the Kuningan region, West Java, there are intellectual figures who are active in the field of education. This thesis aims to find out how KH. Sahal Suhana in driving education in the Kuningan Regency area, West Java in 1994-2016. This research uses historical research methods. The steps include heuristics, verification, interpretation, and historiography. The results of this research are the role of KH. Sahal Suhana, a person who was not born from Kyai descent, was able to take part in becoming a Kyai by becoming the pioneer of the founder of the largest Modern Islamic Education in Kuningan Regency, West Java and growing rapidly, including the Husnul Khotimah Foundation and the Al-Multazam Husnul Khotimah Islam ic Education Foundation. As a pioneer figure who is active in the world of education, he has succeeded in creating new breakthroughs in eliminating the negative stigma of Islamic boarding schools, such as dirty students, dirty water, always wearing sarongs, lagging behind in technology and other problems. In modernizing Islamic education through the Islamic Boarding School KH. Sahal Suhana has succeeded in changing the public's mindset towards the negative stigma of Islamic boarding schools, and in the curriculum has succeeded in developing science and technology for the students, and in terms of facilities and infrastructure has succeeded in completing the foundation's facilities to support learning.